Penilaian Efektivitas Metabolit Sekunder Trichoderma harzianum dalam Menghambat Pertumbuhan Colletotricum capsici dan Cercospora capsici : Kajian In Vitro - Baida Watngil; A. Marthin Kalay; Abraham Talahaturuson; Costanza Uruilal (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2024)
The cultivation of chili plants is often faced with obstacles such as disease attacks, especially anthracnose disease caused by the fungus Colletotricum capsici and leaf spot disease caused by the fungus Cercospora capsici. This study aimed to determine the effective concentration of T. harzianum secondary metabolites (MSTh) in inhibiting the growth of Colletotricum capsici and Cercospora capsici in vitro. The experiments used various MSTh concentrations: 0%, 10%, 20%, 30%, 40%, and 50%. The research results found that administration of MSTh could inhibit the growth of Colletotricum capsici and Cercospora capsici in vitro. Giving MSTh at a concentration of 10% can significantly inhibit the growth of Colletotricum capsici and Cercospora capsici compared to without MSTh. The effective concentration indicated by the percentage value of inhibitory power and colony weight reduction is an MSTh concentration of 40% with a growth inhibition of Colletotricum capsici of 89.49% and an MSTH concentration of 50% with a growth inhibition of Cercospora capsici of 57.78%.